Strategi Employer Branding Perusahaan X dalam Membentuk Brand Associations (Studi Kasus pada Program Internship ‘X Star’ dan ‘X Center’ dalam Membentuk Brand Associations) - Yulianna, Rica (Universitas 17 Agustus 1945 Surabaya, 2021)
X Company is one of the financial companies in Indonesia that has strategy of external employer branding in the form of internship program. The internship of X Company targets students also campuses as potential employees. This strategy done to shaping and establishing corporate brand associations through several tactis that described deeper in the following research. This research is a descriptive qualitative research with a case study method. Methods for data collection was carried out through participatory observation, digital literature studies, and interviews with four resources as the implementer of internship program. The results of this study indicate that the internship of X Company has several tactics in the implementation. Those tactics such as the concept of Career Development, activity of introduction, the concept of Career Partner, and economic value factors. Finally, strategy of internship in X Company shape and establish brand associations by involving cognitive, conative, affective aspects as well as functional associations and emotional associations. Keywords: strategy, employer branding, internship, brand associations